Development of surface discharge along a dielectric with large dielectric constant in gas in the nanosecond range; Journal of Applied Mechanics and Technical Physics; Vol. 14, № 1 - Koval'chuk B. M.; Kremnev V. V.; Mesyats G. A. Gennady Andreyevich; Yurike Ya. Ya. (1973, 1973)
В фонде НТБ ТПУ отсутствует